2020
DOI: 10.1097/mpg.0000000000002909
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Success and Failure of Weaning Children From Prolonged Enteral Nutrition

Abstract: Objectives:The aims of the present study were to assess the efficacy of a tube weaning program, and to identify factors associated with success and failure. Methods: This was a retrospective cohort study including all pediatric patients on enteral nutrition (EN) for !6 months for whom at least 1 attempt of weaning was performed in a single tertiary referral center from 2012 to 2017, with a minimum follow-up of 6 months after EN discontinuation. Weaning program was individualized to each child. Weaning success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Long-term enteral feeding has substantial social and healthcare costs, but it is hard to develop expertise in managing tube dependency, as it presents relatively rarely in most centres. Our earlier study6 and a recent larger case series using a similar outpatient feed reduction regime by Dipasquale et al 3 showed that children could be safely tube weaned. In this new series, we consider the role weight loss plays in how long the process takes.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Long-term enteral feeding has substantial social and healthcare costs, but it is hard to develop expertise in managing tube dependency, as it presents relatively rarely in most centres. Our earlier study6 and a recent larger case series using a similar outpatient feed reduction regime by Dipasquale et al 3 showed that children could be safely tube weaned. In this new series, we consider the role weight loss plays in how long the process takes.…”
Section: Discussionmentioning
confidence: 79%
“…We successfully weaned 90% of children, compared with 70% in Dipasquale et al's series, where 11% of wean attempts feeds were restarted because of rapid weight loss. 3 The association of weight loss with initially higher BMI has not been reported before, but in another case series, children who failed to stop feeds had markedly higher BMI at baseline (+1 SD), compared with those successfully weaned (−0.41). 16 Thus, there is a risk that high initial weight loss will lead to termination of the weaning process before children have lost enough of their surplus weight to develop an interest in food.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Other established feeding programs include the following: the Newborn Individualized Developmental Care & Assessment Program (NIDCAP) ( 4 ). The Sequential Oral sensory (SOS) Approach to Feeding ( 5 ), the Satter Eating Competence Model ( 6 ), and programs worldwide in places such as Austria ( 7 ), the United States ( 8 ), the Netherlands ( 9 ), and France ( 10 ). Many programs consist of intensive outpatient or even two to three weeklong inpatient stays.…”
Section: Introductionmentioning
confidence: 99%